Uncle’s bread - Zulkifli, Zarif Ikhwan; Mohd Noor, Mohammad Hafizul Akmal; Mohd Nadzeri, Muhammad Naif Irfan; Rossede, Nur Muhammad Aidil Hakim; Ibrahim, Muhammad Syafiq Aiman (2021)
Uncle’s Bread is the business that offers variousity of breads with the best quality and the business not only sold breads but cookies and mini pastries. Our business have selected the target customers at the Kuala Terengganu. The target customers are adults, children, elders and teenagers. We identified that this place was less of bread shops. We also think that our place can be stop center for the people to buy our product before spent their time with friends and family. Our business provide mouth-watering breads and we can guarantee that customers want to try it again. Uncle’s Bread marketing approach is to focus on the quality of our services for our customers. We offer an affordable price for the breads because maybe a few people in Kuala Terengganu have a low income and a low standard family. As a result, we are developing a marketing strategy that gives our shop an appeal, particularly people who not to be able to afford. We will expect that our business will become more developed in the near future because with the new innovation in our breads, the demand will increase not only during occasion but it might be as their daily routine for them to buy it. This will give more advantages for us to make our product more profitable and stable in the long term.